Morphometric analysis of mithun sperm from fresh and frozen-thawed semen - KHAN, M H; SINHA, PAPIYA; PERUMAL, P; HAZARIKA, S B (The Indian Journal of Animal Sciences, 2017)
The present study was conducted to compare various morphometric parameters of mithun sperm (Bos frontalis)in fresh and frozen-thawed semen. Ejaculates (36) from 6 mithun bulls were subjected for cryopreservation with commercial extender (optixel). The semen sample after dilution was cooled gradually from 35°C to 5°C and then frozen in biofreezer under controlled freezing rate. Both fresh and frozen-thawed semen were processed for staining using Eosin-Nigrosin and Giemsa stain and digitized for morphometric evaluation. Mean linear measurements of different parameters, viz. head-length, head-width, head-base, acrosome length, acrosome width, midpiece length, tail length, head shape, head area, head circumference and total sperm length, were taken. Results revealed no difference in various sperm morphometric parameters between fresh and frozen-thawed sperm except the head area which was significantly lower in frozen-thawed sperm. This is the first comprehensive report on mithun sperm morphometry, and it showed little variation in various morphometric parameters when compared to crossbred bull and Murrah buffalo bull sperm.